Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

Recherches sur la transitude au Québec: entre absence et exploitation des savoirs trans - Clark Pignedoli; Maxime Faddoul (Genre, Sexualité et Société, 2019)
En suivant l’approche méthodologique de l’autoethnographie, cet article se penche sur la question de l’exploitation des personnes trans en tant que travailleur·se·s précaires de l’université néolibérale. On met en relief la double dynamique d’effacement et d’exploitation des personnes trans « en tant que trans », en soulignant qu’au sein du biocapitalisme, la transitude produit de la valeur qui peut être extraite afin de donner un nouveau souffle aux processus d’accumulation de la richesse. Les conditions de travail des personnes trans dans le domaine de la recherche sont ainsi surdéterminées par ces nouveaux mécanismes d’extractivisme. En guise de conclusion, on partage certaines stratégies de résistance pour renverser cette double dynamique.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; biolcapitalisme; canada; capitalisme; cours; discipline; exploitation; premier cycle; périodes historiques; québec; régions géographiques; résistance; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; trans; travail; travail gratuit; travail social; université; violences; études de genres

Neoliberal reform and family engagement in schools: An intersectional gender analysis - Nygreen, Kysa (Policy Futures in Education, 2019)
This article presents an exploration of the work of family engagement in a racially- and linguistically-diverse, high-poverty, urban school district in a state of continuous neoliberal reform. Drawing from qualitative research methods, it is argued that family engagement is being reshaped by the imperatives of educational neoliberalization while, at the same time, remaining out of touch with the needs and concerns of families who are racially stigmatized, linguistically diverse, and experiencing extreme economic insecurity. It is further argued that school personnel charged with family engagement carry out exploited, invisible, and emotional tasks that increase in quantity and intensity as the social safety net declines under neoliberalism. Applying an intersectional gender analysis of emotional labor and the re-privatization of social reproduction offers an illustration of how family engagement in neoliberal schools both exploits and reinforces hierarchies of race–class–gender while obscuring these processes through neoliberal discourses of individual responsibilization. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; inégalités; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail émotionnel; états-unis

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (Rapport de recherche / IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences